Gemini/GMOS photometry of intermediate-age star clusters in the Large Magellanic Cloud - Piatti, Andres Eduardo (2014)
We present Gemini South GMOS g, i photometry of 14 intermediate-age Large Magellanic Cloud (LMC) star clusters, namely: NGC 2155, 2161, 2162, 2173, 2203, 2209, 2213, 2231, 2249, Hodge 6, SL 244, 505, 674, and 769, as part of a continuing project to investigate the extended main-sequence turn-off (EMSTO) phenomenon. Extensive artificial star tests were made over the observed field of view. These tests reveal the observed behaviour of photometric errors with magnitude and crowding. The cluster stellar density radial profiles were traced from star counts over the extent of the observed field. We adopt cluster radii and build colour–magnitude diagrams (CMDs) with cluster features clearly identified. We used the cluster (g, g − i) CMDs to estimate ages from the matching of theoretical isochrones. The studied LMC clusters are confirmed to be intermediate-age clusters, which range in age 9.10 < log(t) < 9.60. NGC 2162 and NGC 2249 look like new EMSTO candidates, in addition to NGC 2209, on the basis of having dual red clumps.